21st Century Global and Regional Surface Temperature Projections. Issue 12 (14th December 2022) - Ma, Nicole; Jiang, Jonathan H.; Hou, Kennard; Lin, Yun; Vu, Trung; Rosen, Philip E.; Gu, Yu; Fahy, Kristen A.
Abstract: Many countries and regions across the globe broke their surface temperature records in recent years. Recent crippling heat waves swept across the Earth, further sparking concerns about the impending arrival of "tipping points" later in the 21st century. This study analyzes observed global surface temperature trends in three target latitudinal regions: the Arctic Circle, Tropics, and the Antarctic Circle. We show that global warming is accelerating unevenly across the planet, with the Arctic warming at more than three times the average rate of our world. We also analyzed the reliability of latitude‐dependent surface temperature simulations from a suite of Coupled Model Intercomparison Project Phase 6 (CMIP6) models and their multi‐model mean (MMM) by comparing their outputs to observational data sets. We selected the best‐performing models based on their statistical abilities to reproduce historical, latitude‐dependent values adapted from these data sets. The surface temperature projections were calculated from ensemble simulations of the Shared Socioeconomic Pathway 2–4.5 (SSP2–4.5) by the selected CMIP6 models. We estimate the calendar years of when surface temperatures will increase by 1.5, 2.0, and 2.5°C relative to the preindustrial period, both globally and in the three target regions. Our results reaffirm a dramatic, upward trend in projected surface temperatures, with unprecedented acceleration in the Arctic Circle, which could lead to catastrophic consequences across the Earth. Further studies are necessary to determine the most efficient solutions to reduce global warming acceleration and maintain a low SSP, both globally and regionally. Key Points: Observational data sets and CMIP6 models were used in this study to determine regional surface temperature projections for the 21st century Acceleration in Arctic temperature increase is found to reach 6°C above preindustrial levels by the end of the 21st century Evaluating when "tipping points" will be reached in different regions is a key in planning solutions to curb this pressing issue